ANALYSIS OF FACTORS AFFECTING CASH DIVIDEND POLICY - Sarwono, Benediktus; As’ari, SE., MM, Hasim (Accounting, 2009)
This research was conducted on manufacturing companies to distribute cash dividends in the period 2002 to 2005. Sampling was done by random sampling and samples obtained during the period of 30 manufacturing companies that meet the sampling criteria. The purpose of this study was to determine whether the six factors (cash flow, company size, growth, capital structure, stock price, and number of shareholders) have influence and good relations partially or jointly against the amount of cash dividends. Data used in this study are secondary data obtained by researchers come directly to the secondary data was the JSE TRAVELER UII and PPA UGM using the method of documentation and literature. The data were processed with the program SPSS 10 For Windows. The results of the research is obtained that cash flow, company size, and growth firms have a significant influence on the amount of cash dividends. Meanwhile, capital structure, stock price, and number of shareholders do not have a significant influence on the amount of cash dividends. Keywords: Manufacturing Company, Cash Dividend